The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0001-3765201720170190
|View full text |Cite
|
Sign up to set email alerts
|

Mercury content in the fur of jaguars (Panthera onca) from two areas under different levels of gold mining impact in the Brazilian Pantanal

Abstract: The Pantanal is the largest inland wetland in the world and is under increasing anthropogenic threats, including long-term regionally intensive gold mining practices. Gold mining activities are known to cause the release of harmful pollutants such as mercury (Hg) to the surrounding environment. Jaguars (Panthera onca (Linnaeus, 1758)) are apex predators, and therefore show great potential to accumulate Hg by biomagnification. We hypothesize that total Hg content in the fur of jaguars from two sites within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
0
11
0
2
Order By: Relevance
“…We have not found existing reports on levels of trace elements in the hair of European wildcats. Measured THg in felids in non-contaminated areas does not exceed 30 mg kg −1 dw (May Júnior et al 2017), while in contaminated areas it ranges from 46 to 673 mg kg −1 dw (Kitamura 1968;May Júnior et al 2017). In this study, average THg concentration in European wildcats was 0.73 mg kg −1 dw, about 40x lower than in the hair of jaguars from a reference area in Brazil.…”
Section: Discussionmentioning
confidence: 49%
“…We have not found existing reports on levels of trace elements in the hair of European wildcats. Measured THg in felids in non-contaminated areas does not exceed 30 mg kg −1 dw (May Júnior et al 2017), while in contaminated areas it ranges from 46 to 673 mg kg −1 dw (Kitamura 1968;May Júnior et al 2017). In this study, average THg concentration in European wildcats was 0.73 mg kg −1 dw, about 40x lower than in the hair of jaguars from a reference area in Brazil.…”
Section: Discussionmentioning
confidence: 49%
“…Bioaccumulation of MMHg to top predators from aquatic sources is well documented 3033 , which is largely due to the prevalence of anaerobic microbes in aquatic systems, plus the numerous food web positions that allow for efficient trophic transfer of MMHg. For terrestrial predators within food webs of terrestrial origins, the risk is thought to be lower, with the exception of sites close to highly polluted active mines 34 and runoff from legacy mining activity 35 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, considering the sum of the HR extents and the total area overlapped with the PAs, we found that 20% of the HR extent matched the PAs. Notably, jaguars coexist with different levels of anthropic pressures outside the PAs [4][5][6][7][8][9][10][11][12][13] . Jaguar distribution range has been restricted to 63% of the Pantanal 5 and even more restricted in the UPRB 77 .…”
Section: Fires As a Threat To Jaguarsmentioning
confidence: 99%
“…However, jaguar populations are increasingly threatened due to the accelerated intensification of land use in these areas. The main threats to jaguar conservation 1,5 are habitat loss 4 , prey poaching 4 , retaliation for livestock depredation [6][7][8] , pollution from mining and pesticides 9 , increased agricultural activities 10 and human infrastructure (e.g., increased roadkill rates) [11][12][13] . Although fire is typically considered a threat to a small proportion of the overall jaguar population 1 , the unprecedented severity of the 2020 fires in the Pantanal [14][15][16][17][18] suggests that fire may be an unaccounted risk to jaguar conservation in this biome.…”
Section: Introductionmentioning
confidence: 99%